Interreg 2 seas Project: Health For Dairy Cows, H4DC. Issue 7 (10th July 2020) - A. Ribeiro, Claudia; Pinto, Pedro; J. Warren, Christopher; Vlandas, Alexis; Vuylsteke, Isabelle; Canniere, Evi; Dellevoet, Martine; Roemen, Janine; Bourgeois, Anne; Leruste, Helene; Roblin, Maud; Windal, Feryal; et al.
Abstract : Cryptosporidium spp. are microbial parasites that infect the gastrointestinal tract of humans and many animals, causing cryptosporidiosis, a disease characterised by acute watery diarrhoea. In dairy farms, C. parvum is the most common species in calves, leading to high mortality rate, stunted growth, and consequently high economic losses. Trade between farms and breeding centres is a major risk factor in the spread of such parasites, posing a threat to other farms worldwide as well as to human health. This problem is aggravated by the lack of good breeding practices, efficient detection tools, and lack of effective anti-cryptosporidial drugs. To address cryptosporidiosis in dairy farms, we have established the 'Health For Dairy Cows (H4DC)' consortium in order to tackle some of the aforementioned issues. Herein, we will present preliminary data from a 3-step strategy: 1)Dissemination of pilot farms in France, Belgium, The Netherlands and England. This collaboration will serve to test the effect of new husbandry practices in the occurrence of Cryptosporidium, which will aim to decrease Cryptosporidium incidence and ultimately decrease the economic burden of cryptosporidiosis. 2)These pilot farms will later be used as testing-grounds of the low-cost and easy-to-use in-situ C. parvum detection tool that will be developed during this project. 3)Development of a cell-based drug-screening system which will be used to screen various drugs and compounds for anti-Cryptosporidium activity. Finally, data from these findings will be used to establish model and strategies in order to transfer the developed technologies to both farmers and biotech/pharmaceutical companies.